The Influence of Implementation of Good Corporate Governance on the Effectiveness Organization of Teenagers Information and Counseling Centers in PIK-Remaja Organization Surakarta Indonesia - Aroran, Farryl Febian; Pratita, Mutya Paramita; Sarwono, Aris Eddy; Rahadhini, Marjam Desma (AIBPM Publisher, 2024)
This research focuses on the influence of implementing Good Corporate Governance on the effectiveness of the Youth Information and Counseling Center in Surakarta. Research was conducted in several areas in Surakarta, including Serengan, Banjarsari, Jebres, Pasar Kliwon, and Laweyan. The aim is to understand more deeply the relationship between aspects of Good Corporate Governance and the effectiveness of the PIK-Remaja organization. This research uses quantitative methods by collecting primary data through interviews using questionnaires. The results show that aspects of Good Corporate Governance such as transparency, accountability, responsibility, independence and fairness have a significant influence on organizational effectiveness.